ZAKAT SEBAGAI SARANA BANTUAN BAGI MASYARAKAT BERDAMPAK COVID-19 - Saputra, Hijrah (Fakultas Ilmu Sosial dan Ilmu Pemerintahan, 2020)
The Signing of a National Disaster (Covid-19) as a National Disaster through Presidential Decree Number 12 of 2020 Determination of Non-Disaster in the Spread of Covid-19 as a National Disaster. All efforts that are being made right now are being carried out by the government through social measures to distribute the outbreak virus, of course, it will have an impact on the community in taking the call. The